POTENTIALLY MEANINGFUL TEACHING UNITS (PMTU) AND THE LEARNING OF OXYRREDUCTION - Gomes, Duliane da Costa (2023)
The search for new strategies that help in the teaching-learning process of chemical concepts is necessary above all to develop contextualized, non-fragmented and meaningful learning. The objective of this work was to evaluate evidence of significant learning of oxidation-reduction concepts from a Potentially Meaningful Teaching Units (PMTU). Seventeen volunteer students from the 2nd year of high school from a public school in Manaus participated in the research, The data collection instruments were conversation circles and activity sheets. The discussion was guided by the Theory of Meaningful Learning, guided by participatory research and data evaluated in a descriptive and interpretive way and by content analysis. Based on the results obtained, it was evident that the use of PMTU, enables and facilitates the process of significant learning, showing evidence of learning concepts such as oxidation, reduction, electron transfer, corrosion, reactivity pointed out in the literature as difficult to assimilate.